Implications and strategies of poor leadership in organizational and community dynamics - Eliyunus Waruwu (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Poor leadership has far-reaching and serious impacts on individuals, organizations, and society as a whole. Research on poor leadership has highlighted a range of its negative implications, including decreased employee well-being, low job satisfaction, and dysfunction in organizational governance. Factors that influence the emergence of poor leadership include organizational culture, ethical climate, destructive leadership, and individual characteristics. Dimensions of poor leadership include toxic behavior, its ethical implications, as well as its negative impact on employee well-being, organizational culture, and performance. It is important to understand and address poor leadership in order to create a healthy work environment and encourage positive leadership practices. With a deeper understanding of the various dimensions and implications of poor leadership, we can develop more effective strategies to identify, address, and minimize its negative impacts.